(untitled) (Web of Teachers: Inderscience Research, 2024)
The systematic activity approach to training future teachers emphasizes the structured integration of theoretical knowledge and practical application, promoting a holistic and dynamic learning experience. This approach, rooted in active learning and constructivist pedagogy, prepares teacher candidates to effectively navigate the complexities of modern classrooms. This article explores the historical and theoretical foundations of the systematic activity approach, reviews contemporary research on its implementation, and highlights its positive impact on teacher preparedness. By integrating active learning strategies and leveraging technology, this approach enhances teacher training programs, fostering critical thinking, problem-solving skills, and reflective practices. The findings underscore the efficacy of systematic activities in bridging the gap between theory and practice, equipping future educators with the competencies necessary for effective teaching.